2019
DOI: 10.1101/777300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cis-regulatory differences in isoform expression associate with life history strategy variation in Atlantic salmon

Abstract: The optimal phenotypes to survive and reproduce in given evolutionary settings are often in conflict, which manifest as trade-offs in life history traits. Genome-wide association studies have been successful in uncovering genome regions controlling for life history trade-offs in a range of species [1][2][3][4][5][6][7][8] . However, lack of functional studies of the discovered genotype-phenotype associations restrains our understanding how alternative life history traits evolved and are mediated at the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…In Atlantic salmon, the vestigial-like family member 3 gene ( vgll3 ) is strongly associated with maturation timing in the wild in both sexes but also exhibits sex-specific maturation effects (Barson et al, 2015; Czorlich et al, 2018). This association between vgll3 and maturation probability has been subsequently validated in one year-old males in common garden settings (Debes et al, 2021; Sinclair-Waters et al, 2021; Verta et al, 2020). This makes vgll3 a potential candidate regulating reproductive axis genes in place of the absent gnrh1 , however, the molecular details of the action of vgll3 on reproductive axis genes has remained unexplored.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In Atlantic salmon, the vestigial-like family member 3 gene ( vgll3 ) is strongly associated with maturation timing in the wild in both sexes but also exhibits sex-specific maturation effects (Barson et al, 2015; Czorlich et al, 2018). This association between vgll3 and maturation probability has been subsequently validated in one year-old males in common garden settings (Debes et al, 2021; Sinclair-Waters et al, 2021; Verta et al, 2020). This makes vgll3 a potential candidate regulating reproductive axis genes in place of the absent gnrh1 , however, the molecular details of the action of vgll3 on reproductive axis genes has remained unexplored.…”
Section: Introductionmentioning
confidence: 81%
“…This makes vgll3 a potential candidate regulating reproductive axis genes in place of the absent gnrh1 , however, the molecular details of the action of vgll3 on reproductive axis genes has remained unexplored. It has already been suggested that vgll3 might affect gametogenesis by regulating cell fate commitment genes (Kjærner-Semb et al, 2018; Kurko et al, 2020), and its repression in salmon testis has been associated with induced onset of puberty (Kjærner-Semb et al, 2018; Verta et al, 2020). A recent study demonstrated that expression of alternative isoforms of vgll3 associates with variation in age at maturity in one-year-old salmon males (Verta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we cannot rule out the possibility that the causal variation driving the vgll3 genotype effect alters the functioning of a different gene, however given the tight genetic linkage of the vgll3-SNPs and vgll3, vgll3 variation is nevertheless strongly associated with maturation timing. Recent functional research also supports this notion -2 vgll3 expression in immature testes of Atlantic salmon differs between vgll3 genotypes, EE and LL (Verta et al 2020), which suggests that SNP variation linked with vgll3 also associates with altered vgll3 function. Further, we cannot exclude the possibility that the causal variation may regulate both vgll3 and akap11 given their close proximity.…”
Section: Resultsmentioning
confidence: 78%
“…We collected immature male gonads from five 11-12-month-old male Atlantic salmon raised in common-garden conditions (see details in (Verta et al 2020). Fish were euthanized using an overdose of MS-222, followed by decapitation.…”
Section: Methodsmentioning
confidence: 99%